Modeling the effects of levee setbacks on flood hydraulics - Roderick W. Lammers; Matthew Chambers; Brian P. Bledsoe (Journal of Flood Risk Management, 2024)
Abstract Relocating levees further back from river channels to increase river–floodplain connection can reduce flood stages and provide a host of co‐benefits. Modeling case studies show the significant potential of large levee setbacks for reducing flood stages; however, the difficulty of comparing between these case studies limits our understanding of how the hydraulic effects of setbacks vary in different settings. We filled this research gap by systematically modeling the hydraulic effects of setbacks across a range of river and flood conditions. We used unsteady, 1D Hydrologic Engineering Center‐River Analysis System models to quantify changes in flood stage, channel velocity, and sediment transport capacity for various setback sizes with different river slopes, widths, floodplain roughness, and flood sizes (peak flows) and durations. Setbacks reduce flood stages within the setback, as well as up‐ and downstream. Channel velocity and sediment transport capacity both increased upstream and decreased within the setback. Channel slope, flood size, and flood duration had the largest influence on hydraulic changes. There are diminishing returns in hydraulic effects with increasing setback size. These results can help guide the design and prioritization of levee setback projects and help set reasonable expectations for the scale of changes to flood hydraulics relative to the size of the reconnected floodplain.